The effects of height and frequency of previous defoliation on nodulation, nitrogen fixation and regrowth of phasey bean - Wan Othman, Wan Mohamad; Asher, C. J. (Universiti Pertanian Malaysia, 1987)
Inoculated seeds of phasey bean (Macroptilium lathyroides cv. Murray) were sown in a sand culture in a naturally-lit glasshouse, and imgated daily with nitrogen-Free nutrient solution. At early flowering, the plants were either left uncut or cut at node 5 (high) or node 1 (low), retaining the corresponding residual leaf areas of 74, 11 and Ocm 2 plant 1respectively. Following this initial cutting, new shoots were individually harvested at the frequency of one, two, three, four or eight times over a penriod of 56 days in Phase 1. Total dry weight of new shoots, seed yields and nitrogen concentrations in the herbage were assessed. A II plants were allowed to regrow during the next 21-day recovery period in Phase 2. Then, the root systems and plant tops were harvested. Nodulation,nitrogen fixation (total N) and regression analyses on s011Je plant parameters were computed. In Phase 1, cumulative yields of new shoots harvested following high or low-level cutting declined significantly with increasing harvesting frequency, but yield reductions due to low-level cutting were detected only under high harvesting frequencies. In Phase 2, recovery growth was always better following high than low-level cutting, but unexpectedly, the various harvesting frequencies had no effect on recovery growth following high cutting. After low-level cutting, high or low harvesting frequency reduced recovery growth compared with moderately frequent defoliation (two harvests in 56 days), which coincided with early flowering on the new top growth. Recovery growth had a positive linear correlation (r = 0.98 ***) with nitrogen fixation, which was also linearly correlated with nodulation. These results are briefly discussed with reference to the current concept that regrowth of nodulated forage legumes is largely dependent on symbiotic nitrogen fixation.